Energy efficiency in virtualized data center - Karamat Khan, Tehmina; Tanveer, Mohsin; Shah, Asadullah (Science Publishing Corporation, RAK Free Trade Zone, 2018)
Industrial and academic communities have been trying to get more computational power out of their investments. Data centers have currently received huge attention due to its increased business value and achievable scalability on public private clouds. Infrastructure and applications of modern data center is being ritualized to achieve energy efficient operation on servers. Despite of data center advantages on performance, there is trade off between power and performance especially with cloud data centers. Today, these cloud applications based organizations are facing many energy related challenges. In this paper, through survey it has been analysed how virtualization and networking related challenges affects energy of data center with suggested optimization strategies.